Combination of Bacterial‐Photothermal Therapy with an Anti‐PD‐1 Peptide Depot for Enhanced Immunity against Advanced Cancer. (22nd October 2019) - Chen, Wenfei; Guo, Zhaofei; Zhu, Yining; Qiao, Nan; Zhang, Zhirong; Sun, Xun
Abstract: Photothermal therapy (PTT) is a promising cancer treatment, but it has so far proven successful only with relatively small subcutaneous tumors in animal models. Treating larger tumors (≈200 mm 3 ) is challenging because most PTT materials do not efficiently reach the hypoxic, avascular center of tumors, and the immunosuppressive tumor microenvironment prevents T cells from fighting against residual tumor cells, thereby allowing recurrence and metastasis. Here, the widely used PTT material polydopamine is coated on the surface of the facultative anaerobe Salmonella VNP20009, which can penetrate deep into larger tumors. The coated bacteria are intravenously injected followed by near‐infrared laser irradiation at the tumor site, combined with a local inoculation of phospholipid‐based phase separation gel containing the anti‐programmed cell death‐1 peptide AUNP‐12. The gel releases AUNP‐12 sustainably during 42 days, maintaining the tumor microenvironment as immunopermissive. Using a mouse model of melanoma, this triple combination of biotherapy, PTT, and sustainable programmed cell death‐1 (PD‐1) blockade shows high efficiency on eliciting robust antitumor immune responses and eliminating relatively large tumors in 50% of animals within 80 days. Thus, the results shed new light on a previously unrecognized immunological facet of bacteria‐mediated therapy, and this innovative triple therapy may be a powerful cancer immunotherapy tool. Abstract : A novel triple therapy is developed for healing relatively large‐sized melanoma. With only one injection of polydopamine‐coated bacteria, one NIR laser irradiation, and one inoculation of phospholipid‐based phase separation gel containing the antiprogrammed cell death‐1 peptide AUNP‐12, this combination strategy targets the hypoxic, avascular center of tumors, and triggers potent antitumor immune responses in vivo.